PLATFORM CAPITALISM AS THE SOURCE OF DIGITAL RENTIER’S SUPERPROFIT - I. M. Stepnov (MGIMO University Press, 2018)
The need for a critical understanding of digitalization in the modern economic structure led to the research relevance. The author’s hypothesis about the predominance of platform capitalism in modern economic relations based on K. Marx’s theory is formulated. The authors believe that the «digital economy» concept does not reflect the essence of the processes in terms of the theory of capitalist development, economic interaction, the dilemma solution of coordination and competition in the economy. Significant indications of the modern economy identification are the platforming and distributing, revealing not technical solutions, but features of economic interaction and priority of management decisions. The distributing is focused on the advantages of the Small Data digital economy, based on the market freedom, market relations and independence of market agents; the platforming characterizes the possibilities of digitalization to reduce transaction costs and monetization of communication relations. The key indication of platform capitalism is the markets design («design of matching markets» by A. Roth) that operate on the basis of digital platforms and provide communication and interaction of market participants. The key elements that modernize the classical understanding of capitalism are identified: 1) the transfer of services to a new sphere – the platform, with the max complete cycle, including payment; 2) the change in the form of hiring workers to provide services – through the platform, including part-time employment; 3) the main source of profit, as well as the object of the operation, becomes information, and then info-communication. An original approach to the identification of platform capitalism as an economic system in which economic agents carry out property ownership on the platforms basis, transferring the organizing process to the contractor, distancing themselves from direct participation in the process and receiving rent from the accumulated by the platform information data and communication solutions is proposed. The possibility of rent from information and channels of its distribution analysis allowed to identify the subject of investment relations – the digital rentier, which receives the main income from investments in the objects of the digital economy – platforms, which have already monetized the usefulness of the presented functionality and data. The authors proved that the limitations of the ability to business control should lead to the fact that the expected return rate from the digital platform’s investments of the rentier should be significantly higher than for the shareholder. The article is debatable, the provisions and conclusions require further research.